Mandaluyong business directory 1992-1993. (Kilter Enterprises, 1993)
Considered as an important medium through which new products, services and technologies offered by businesses in Mandaluyong can be showcased to generate greater public interest, investment and utility, and the development of Mandaluyong as a strategic investment center in Manila. This directory lists companies alphabetically according to their products and services. That directory also features some facts about the city: distribution of establishments, commercial and industrial areas, statements of annual revenues, local banks, schools, hospitals, and a directory of the different departments of the Municipality of Mandaluyong.